A vitamin B12 conjugate of exendin‐4 improves glucose tolerance without associated nausea or hypophagia in rodents. Issue 5 (20th February 2018) - Mietlicki‐Baase, Elizabeth G.; Liberini, Claudia G.; Workinger, Jayme L.; Bonaccorso, Ron L.; Borner, Tito; Reiner, David J.; Koch‐Laskowski, Kieran; McGrath, Lauren E.; Lhamo, Rinzin; Stein, Lauren M.; De Jonghe, Bart C.; Holz, George G.; et al.
Abstract : Aims: While pharmacological glucagon‐like peptide‐1 receptor (GLP‐1R) agonists are FDA‐approved for treating type 2 diabetes mellitus (T2DM) and obesity, a major side effect is nausea/malaise. We recently developed a conjugate of vitamin B12 (B12) bound to the GLP‐1R agonist exendin‐4 (Ex4), which displays enhanced proteolytic stability and retention of GLP‐1R agonism. Here, we evaluate whether the conjugate (B12‐Ex4) can improve glucose tolerance without producing anorexia and malaise. Materials and methods: We evaluated the effects of systemic B12‐Ex4 and unconjugated Ex4 on food intake and body weight change, oral glucose tolerance and nausea/malaise in male rats, and on intraperitoneal glucose tolerance in mice. To evaluate whether differences in the profile of effects of B12‐Ex4 vs unconjugated Ex4 are the result of altered CNS penetrance, rats received systemic injections of fluorescein‐Ex4 (Flex), Cy5‐B12 or Cy5‐B12‐Ex4 and brain penetrance was evaluated using confocal microscopy. Uptake of systemically administered Cy5‐B12‐Ex4 in insulin‐containing pancreatic beta cells was also examined. Results: B12‐Ex4 conjugate improves glucose tolerance, but does not elicit the malaise and anorexia produced by unconjugated Ex4. While Flex robustly penetrates into the brain (dorsal vagal complex, paraventricular hypothalamus), Cy5‐B12 and Cy5‐B12‐Ex4 fluorescence were not observed centrally, supporting an absence of CNS penetrance, in line with observed reduction in CNS‐associated Ex4 side effects. Cy5‐B12‐Ex4 colocalizes with insulin in the pancreas, suggesting direct pancreatic action as a potential mechanism underlying the hypoglycaemic effects of B12‐Ex4. Conclusion: These novel findings highlight the potential clinical utility of B12‐Ex4 conjugates as possible future T2DM therapeutics with reduced incidence of adverse effects.